Plant adaptation to different climates shapes the strengths of chemically mediated tritrophic interactions. (10th July 2019) - Kergunteuil, Alan; Humair, Lauréline; Münzbergová, Zuzana; Rasmann, Sergio
Abstract: How plant traits evolve along geographical and climatic gradients has recently received increased attention because of anticipated climate change and associated shifts in insect distribution, whether they are herbivores or predators. This issue is particularly relevant for traits related to growth and anti‐herbivore defence of plants, because both sets of traits are closely tied to fitness, and because being sessile organisms, plants tend to experience strong local selection. Despite widespread recognition that the abiotic environment imposes selection on plant traits, how temperature and water availability independently select for allocation to growth and defence against herbivores is not well‐resolved, and even more so, when considering under‐ground herbivory and tritrophic interactions involving plant herbivores and their predators. To address heritable, climate‐driven variation in root traits mediating tritrophic interactions, we performed a common garden experiment with four populations of common red fescue ( Festuca rubra ) encompassing the four corners of a precipitation by temperature gradient matrix. We found that plants originating from wetter and warmer conditions, in addition to producing more biomass, also produced a blend of volatile organic compounds more attractive for predatory nematodes of root insect herbivores. Moreover, across populations, variation in nematode attraction was mediated by balancing the emissions of attractive and repulsive volatile compounds. Our work builds towards better understanding how plant adaptation to climate interacts with adaptations to herbivores and their predators. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.